Surgical anatomy of greater occipital nerve and its relation to occipital artery - Nancy Mohamed El Sekily; Ihab Helmy Zedan (Alexandria Journal of Medicine, 2015)
Introduction: The knowledge of the anatomy of greater occipital nerve and its relation to occipital artery is important for the surgeon. Blockage or surgical release of greater occipital nerve is clinically effective in reducing or eliminating chronic migraine symptoms. Aim: The aim of this research was to study the anatomy of greater occipital nerve (GON) and its relation to occipital artery. Also the use of these anatomical measures in local injection of the greater occipital nerve for treatment of migraine. Materials and methods: The study was carried out at the Faculty of Medicine, Alexandria University. The posterior neck and scalp of 25 cadaveric heads were dissected. GON was identified and measured relative to bony landmarks. Delineation of GON and occipital artery relationship was done. Twenty patients suffering from migraine diagnosed according to International Headache Society (IHS) criteria (HIS 2004) were treated using GON blockade. The landmark for GON injection was based on the anatomical study. Treatment was assessed using the visual analogue scale for migraine pain. Results: In the anatomical study, the GON was found in all specimens. The diameter of GON was measured at the lower border of inferior oblique, where it pierced SSC, and after its exit from trapezius muscle. The distance between the point where the GON pierced SSC inferior to the external occipital protuberance (EOP) and lateral to the midline was also measured. The GON was parallel to the occipital artery. The distance between GON and occipital artery was measured. In the clinical study, 20 patients suffering from migraine were treated with 1.5 ml of 0.5% bupivacaine using GON blockade. The landmark for GON injection was based on the anatomical study. For the right GON: the vertical location inferior to EOP ranged from 19.85 mm to 26.9 mm with a mean of 23.1 mm. The lateral location from EOP ranged from 11.03 mm to 14.65 mm with a mean of 13.4 mm. For the left GON: the vertical location inferior to EOP ranged from 16.89 mm to 29.5 mm with a mean of 22.1 mm. The lateral location from EOP ranged from 10.89 mm to 15.31 mm with a mean of 14.1 mm. Pain was improved in 70% of patients within the first hour after the first injection. After 1 month, 60% of patients still showed improvement. Conclusion: The knowledge of the anatomy of greater occipital nerve and its relation to occipital artery is important for the surgeon. Blockage or surgical release of greater occipital nerve is clinically effective in eliminating chronic migraine headache.